Inovasi Penyemaian Pakcoy Menggunakan Karton Telur Bersama Ibu-Ibu di Desa Sinar Bhakti - Virna Lestia; Nadia Oktarina; Enji Anjela; Nurhalimah Nurhalimah; Rr Dimas Veronica Priharti (Cakrawala: Jurnal Pengabdian Masyarakat Global, 2025)
The main problem faced by women in Sinar Bhakti Village is the lack of knowledge and skills in pakcoy seedling using efficient and eco-friendly growing media. Egg cartons were chosen as an innovative solution due to their affordability, availability, and ability to retain the moisture needed by the seeds. This community service program aimed to enhance participants' skills in utilizing egg cartons for pakcoy seedling to support sustainable household farming. The methods used included demonstration-based training and hands-on practice, complemented by interactive discussions on local resource management. The results showed that participants were able to understand and effectively apply seedling techniques, with egg cartons proving to accelerate early growth and minimize water usage. In addition to improving individual skills, this activity fostered awareness of the importance of local innovation and waste utilization for family economic development. It contributed to local food security and strengthened the role of women in Sinar Bhakti Village in creatively utilizing available resources.